PEMBERDAYAAN ANGGOTA PKK DESA MAMPUN BARU MELALUI PELATIHAN ECOPRINT MENGGUNAKAN TANAMAN LOKAL - Arista Ratih; Eni Yulianti; Pitri Handayani; Leni Marlina; Eko Wulandari; Amrianto; Renov Hastasia; Juanita Hibatullah; Widia Putri Febriani (AbdiMasya | Hira Institute, 2025)
This community service activity aims to improve the knowledge, attitudes, skills, and economic motivation of PKK members of the new Mampun village through local plant-based ecoprint training. The activity was held in Mampun Village only on December 5, 2025 with a total of 12 participants PKK members. The method used is participatory training through lectures, demonstrations, and hands-on practice. The evaluation was carried out using pre-test and post-test questionnaires which included four aspects, namely knowledge, attitudes, skills and confidence, as well as motivation for economic empowerment. The results show an improvement in all aspects. The knowledge aspect increased from 63.33% to 90.67%; attitude from 65.33% to 90.67%; skills from 58.67% to 88.00%; and economic motivation from 62.67% to 88.67%. These results show that ecoprint training is effective in increasing the capacity and independence of PKK members in Mampun Baru based on local potential and creative economy.